Biodiversity Resources and Livelihoods: A Case from Lamabagar Village of Middle Nepal - Shrestha, Uttam Sagar (NUTA Journal, 2019)
The biodiversity resources are integral part of the livelihoods of residents of Lamabagar Village Development Committee. Over the last three decades, the number of species has been decreasing due to infrastructure developments- roads, hydropower’s. Reportedly, 277 species of plants 24 species of mammals and 37 species of birds were recorded in 2003 has come down to 244 species of plants, 20 species of mammals and 32 species of birds only in the present study. It has led mis-balance between biodiversity conservation and livelihood strategy. The present paper tries to discuss on overview of plant and animal diversity between 2003-2012, common relationship between bio-diversity resources and their implication in the livelihood, conservation issues and their threats. The findings of the work are based on the fieldwork carried out field survey between 2003 and 2012.